Plantas medicinales y alimentos funcionales usados como recursos contra Covid-19 en una población andina del Perú - Villena-Tejada, Magaly (2021)
Abstract The objective of this research was to identify those medicinal plants and functional foods that the population of Cusco, located in the Peruvian Andes, use as resources to cope with COVID-19 either for prevention or as an adjuvant to treatment with drugs. A descriptive, non-experimental and cross-sectional research was developed. The study population consisted of inhabitants over 20 and under 70 years of age, of both exes from the districts of Cusco, San Jeronimo, San Sebastian, Santiago and Wanchaq in the city of Cusco, Peru. A virtual survey was applied to 1747 inhabitants, for which a questionnaire was designed and elaborated with 07 items whose content was validated by 10 expert judges using Aiken’s V (Aiken’s V > 0.90). The data collected were exported to a database in Microsoft Excel. This research work was reviewed and approved by the Research Bioethics Committee of the National University of San Antonio Abad del Cusco. The results obtained show that the medicinal plants most used by the population studied were eucalyptus (70.2%), kion (68.3%), garlic (58.8%), matico (49.6%), chamomile (34.0%) and coca (21.6%). The functional foods consumed by the population include lemon (79.1%), kion (65.3%), orange (62.2%), honey (63.5%), onion (52.4%), avocado (40.2%), broccoli (35.8%),fish (35.5%) and tarwi (32.5%) for prevention, symptom relief and as an adjuvant in the treatment with drugs for COVID-19.